2020
DOI: 10.1177/1321103x20935200
|View full text |Cite
|
Sign up to set email alerts
|

Activating gender: How identity affects students’ perceptions of music activities

Abstract: In adolescence, many students align their music participation choices with the expectations for their gender group. While cultural norms may explain gender disparities in music activities, there is no empirical evidence of how gender salience may influence students’ perceptions of music activities. The purpose of this study was to experimentally test the influence of gender salience on adolescents’ perceptions of music activities. Using a quasi-experimental design, middle school participants ( N = 246) were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Boys' musical identities in the past have been identified as "at risk" (Lamont, 2002, p. 56), and significant research has been devoted to the "missing males" (Koza, 1993) in music and singing (Freer, 2007(Freer, , 2010Harrison, 2005Harrison, , 2007Harrison, , 2008Harrison, , 2009Harrison, , 2010Harrison et al, 2012;Watson et al, 2017). Research has also reported on the differences in music participation more broadly between genders during adolescence (Kelley, 2021;McPherson et al, 2015). Other studies have found that boys begin school with the same musical and singing competency as girls (e.g., Barrett, 2012;Freer, 2015;Harrison & Young, 2017;Tafuri, 2008;Welch et al, 1996).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Boys' musical identities in the past have been identified as "at risk" (Lamont, 2002, p. 56), and significant research has been devoted to the "missing males" (Koza, 1993) in music and singing (Freer, 2007(Freer, , 2010Harrison, 2005Harrison, , 2007Harrison, , 2008Harrison, , 2009Harrison, , 2010Harrison et al, 2012;Watson et al, 2017). Research has also reported on the differences in music participation more broadly between genders during adolescence (Kelley, 2021;McPherson et al, 2015). Other studies have found that boys begin school with the same musical and singing competency as girls (e.g., Barrett, 2012;Freer, 2015;Harrison & Young, 2017;Tafuri, 2008;Welch et al, 1996).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In conclusion, there are limited studies examining musicians and self-compassion (Kelley & Farley, 2019;Sigurðardóttir, 2020); more research is needed to build on these findings to determine how self-compassion operates in relation to MPA. Further research is also warranted with varying ages and performance levels.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Kelley and Farley (2019) examined this topic to determine whether college-level music majors had levels of self-compassion that differed from other majors; they found no difference between music and non-music majors. While Kelley and Farley (2019) revealed a relationship between the self-compassion and MPA in music majors, this was found only after a blunt follow-up question that broadly asked participants if they experience MPA in a dichotomous prompt. Another study found a relationship between MPA and the self-compassion construct of over-identification (Sigurðardóttir, 2020).…”
mentioning
confidence: 99%